ANALISIS PENGARUH KEPEMILIKAN PEMERINTAH, KEPEMILIKAN ASING, RISIKO LIKUIDITAS DAN RISIKO KREDIT TERHADAP KINERJA KEUANGAN BANK - Sabrina, Farah Nur; Muharam, Harjum (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to analyze the effect of different types of ownership, liquidity risk and credit risk on bank financial performance. State ownership and foreign ownersip were used as the ownership indicators. Liquid Asset to Total Asset (LATA), Non Performing Loan (NPL) and Return On Asset (ROA) ratio were used as the proxied of liquidity risk, credit risk and financial performance. The Population that was used in this research consisted of all conventional commercial banks which published the financial statements during 2007-2011. After passed the purposive sampling method there were 51 banks obtained as samples. The data analysis technique used is descriptive statistic, panel regression test with common effect model, classical assumption test and hypotheses test. The result of this research showed that independent variable consisted of state ownership, foreign ownership, LATA, NPL and control variable bank size all have significant impact on ROA. Research also found that state banks and foreign banks have a better level of profitability than private domestic banks.